Catalytic chemical reduction of nitrate from simulated groundwater using hydrogen radical produced on the surface of palladium catalyst supported on the magnetic alumina nanoparticles. Issue 4 (August 2018) - Rahimi, Erfan; Sajednia, Ghazal; Baghdadi, Majid; Karbassi, Abdolreza
Graphical abstract: Highlights: F e 3 O 4 @ A l 2 O 3 was introduced as an efficient support for palladium catalyst. The catalyst exhibited good performance for nitrate removal from groundwater. The alumina coating had a considerable impact on the catalyst performance. Catalyst performance decreased slightly after three cycles of the regeneration. The maximum removal efficiency and N2 selectivity were 96 and 95%, respectively. Abstract: In this research, the performance of palladium catalyst coated on an efficient support, Fe3 O4 @Al2 O3, was investigated for the removal of nitrate from groundwater in a catalytic chemical reduction process. The hydrogen gas was produced using an electrochemical cell with two graphite electrodes. The material characterization was performed using FE-SEM, TEM, XRD, and VSM analyses. The alumina coating had a considerable impact on the removal efficiency. An optimum rate of 8 wt% was selected for loading of palladium on the support. The Box-Behnken of response surface methodology was applied to optimize the reduction process and investigate effects of variables (time, nitrate concentration, and catalyst dosage) and their interactions on the response. Furthermore, the impact of current density as a parameter affecting the electrochemical production of hydrogen gas was investigated. A quadratic model with the maximum removal efficiency of 96% and N2 selectivity of 95% was obtained at an initial nitrate concentration of 150 mg L −1, catalyst dosage of 2 g L −1, and reaction time of 90 min. Moreover, using the catalyst dosage of 1.3 g L −1, the nitrate concentration decreased from 150 mg L −1 to the maximum contaminant level (MCL) of 50 mg L −1 after the reaction time of 30 min, pH 7, and a current density of 25 mA cm −2 . The investigation of catalyst performance after three cycles of the regeneration showed that the catalyst regeneration was successful.